2016
DOI: 10.5606/fng.btd.2016.001
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of hospitalized patients in Tepecik Training and Research Hospital Internal Medicine Palliative Care Unit

Abstract: Objectives: This study aims to evaluate the patients hospitalized in palliative care unit of our hospital. Patients and methods: In the study, clinical files of 258 patients (104 males, 154 females; mean age 61.4 years; range 19 to 93 years) hospitalized in palliative care unit of internal medicine clinic of our hospital between 12 June 2013 and 31 December 2014 were retrospectively analyzed. Files of the patients were evaluated regarding sex, age, symptoms, clinical features, diagnosis, and duration of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Respiratory system diseases were the second and cardiovascular system diseases were the third most common causes of hospital admissions (Table -3). In the study conducted by Komaç et al, patients received treatment for malignancy, followed up for the completion of long-term antibiotic therapy, and given treatment for diabetes and complications at rates of 33%, 17%, and 17% respectively (14). The study performed by Turgut et al reported that patients were followed up for malignancy, cerebrovascular diseases, and cognitive disorders at rates of 28.5%, 25.5%, and 17.6%, respectively (15).…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory system diseases were the second and cardiovascular system diseases were the third most common causes of hospital admissions (Table -3). In the study conducted by Komaç et al, patients received treatment for malignancy, followed up for the completion of long-term antibiotic therapy, and given treatment for diabetes and complications at rates of 33%, 17%, and 17% respectively (14). The study performed by Turgut et al reported that patients were followed up for malignancy, cerebrovascular diseases, and cognitive disorders at rates of 28.5%, 25.5%, and 17.6%, respectively (15).…”
Section: Discussionmentioning
confidence: 99%
“…It is not only maintenance done in the last period of life but it is a form of treatment that should be integrated in the treatment for prolonging the life span regardless of the disease stage (2). According to the definition of the World Health Organization, 'the approach aims to early identification, evaluation and treatment of pain and other physical and psychological problems that may occur in people with serious illness, and to increase the quality of life in people with lifethreatening diseases and their families (3).…”
Section: Introductionmentioning
confidence: 99%